Proponemos acciones de concientizacin sobre la violencia familiar - Venegas Mndez, Roxana Catalina (2019)
In this work of professional sufficiency, the theme of family violence is developed, for which a design of a learning session based on the approach of personal development and active citizenship corresponding to the area of Citizen and Civic Personal Development, where Students understand the various manifestations of violence._x000D_ In every family there are situations of joy and sadness that help us and allow us to learn and relate to our environment to face solving problems of daily action._x000D_ In this development process, internal and external events occur that can become family crises disturbing their coexistence, families that cannot solve their problems sometimes end up being mistreated and distancing themselves even from reaching physical violence that can occur without control and with fatal consequences._x000D_ In this sense we can observe our reality that family violence rates are increasing, conflicts that are damaging the integral development of the most vulnerable children and adolescents who, when raised in a violent environment, can repeat these patterns and transfer them to their educational environment in where intolerance becomes bullying, for this reason it is necessary to address the problem and be aware of its approach. For this reason, in this learning session we will give information about the manifestations of violence and how we can become aware to stop this situation